eHealth Literacy and Health-Related Internet Use Among Swedish Primary Health Care Visitors: Cross-Sectional Questionnaire Study - Anna Sjöström; Senada Hajdarevic; Åsa Hörnsten; Ulf Isaksson (JMIR Formative Research)
Abstract BackgroundDigitalization has profoundly transformed health care delivery, especially within primary health care, as a crucial avenue for providing accessible, cost-effective care. While eHealth services are frequently highlighted for improving health care availability and promoting equality, it is essential to recognize that digitalization can inadvertently exclude individuals who lack the prerequisites to use eHealth services, that is, those with low eHealth literacy. Previous research has identified lower eHealth literacy among older individuals, those with lower educational levels, and those who use the internet less frequently. However, in a Swedish context, only a few studies have investigated eHealth literacy. ObjectiveThis study investigated eHealth literacy and its association with health-related internet use and sociodemographic characteristics among primary health care visitors. MethodsThis cross-sectional study used a quantitative, descriptive approach. Swedish-speaking patients visiting a primary health care center participated by answering the multidimensional eHealth Literacy Questionnaire (eHLQ) and questions regarding sociodemographic characteristics and internet usage. The study compared mean scores using the Mann-Whitney U ResultsAs a group, the 172 participants rated highest in understanding and engagement with their health (median eHLQ score 3, IQR 2.8‐3.4), as well as in feeling secure about the confidentiality of eHealth services (median eHLQ score 3, IQR 2‐3), while they rated lower in motivation to use eHealth (median eHLQ score 2.6, IQR 2‐3), the suitability of eHealth services to their personal needs (median eHLQ score 2.75, IQR 2‐3), and their perceived ability to understand and use health-related internet information (median eHLQ score 2.6, IQR 2‐3). The logistic regression analysis identified that lower eHealth literacy was associated with older age, particularly in domains related to finding, understanding, and using health-related internet information (odds ratio [OR] 1.02, 95% CI 1‐1.05; PPP ConclusionsOur findings regarding the primary challenges within our sample underscore the importance of developing and tailoring eHealth services to accommodate users’ individual needs better, enhancing motivation for eHealth use, and continuing efforts to improve overall health literacy. These measures, which both eHealth developers and health care professionals should consider, are crucial for addressing the digital divide and expanding access to eHealth services for as many people as possible.